Methyl-CpG-binding domain protein 2 epigenetically represses monocyte HLA-DR expression and promotes immune paralysis in HBV-related acute-on-chronic liver failure - Liu, Xiaoqin; Jiang, Xuhua; Zhang, Xueyun; Hu, Qiankun; Yu, Xueping; Sun, Jian; Lu, Mingqin; Zhang, Jiming; Huang, Yuxian (Frontiers in Immunology, 2026)
Chronic hepatitis B (CHB) is the leading cause of acute-on-chronic liver failure (ACLF) in China and other Asian countries. A defining immunopathological feature of hepatitis B virus-related ACLF (HBV-ACLF) is immune paralysis, which significantly increases susceptibility to secondary bacterial infections and contributes to poor clinical outcomes. A critical determinant of this immunosuppressed state is impaired antigen presentation due to reduced human leukocyte antigen DR (HLA-DR) expression on monocytes; however, the epigenetic mechanism underlying HLA-DR downregulation in HBV-ACLF remains unclear. Methyl-CpG-binding domain protein 2 (MBD2), an epigenetic reader of DNA methylation, has been implicated in the regulation of monocyte-macrophage function in inflammatory diseases, but its role in HBV-ACLF pathophysiology remains to be fully elucidated. In this study, bulk RNA sequencing (RNA-seq) of circulating monocytes from patients with HBV-ACLF showed a transcriptional profile consistent with immune paralysis, characterized by suppressed antigen presentation and inflammatory pathways, alongside pronounced activation of epigenetic regulatory programs. MBD2 expression was subsequently assessed using immunohistochemistry (IHC), reverse transcription quantitative PCR (RT-qPCR), and flow cytometry. Monocyte MBD2 expression was significantly upregulated in HBV-ACLF and was positively correlated with disease severity (r = 0.2797, P = 0.0182), systemic inflammation indices, and clinical prognosis. To delineate the mechanistic role of MBD2, an MBD2-knockout THP-1 cell model was established and subjected to integrated RNA-seq and assay for transposase-accessible chromatin sequencing (ATAC-seq) following differentiation and lipopolysaccharide (LPS) stimulation. The results showed that MBD2 deficiency significantly increased chromatin accessibility and transcriptional activation of genes involved in antigen presentation and pro-inflammatory responses, including pathways related to major histocompatibility complex (MHC) class II synthesis. Concurrently, enhanced promoter accessibility and activation of transcription factors associated with HLA-II class expression were observed, and increased surface HLA-DR expression was confirmed by flow cytometry. Collectively, these findings suggest that MBD2 epigenetically represses HLA-DR expression in monocytes, leading to impaired antigen presentation and immune paralysis, thereby predisposing patients with HBV-ACLF to secondary bacterial infections. Therefore, MBD2 may serve as a novel biomarker for disease progression and a potential therapeutic target for restoring immunological competence in patients with ACLF.